Tau-PET imaging predicts cognitive decline and brain atrophy progression in early Alzheimer’s disease - Lagarde, Julien; Olivieri, Pauline; Tonietto, Matteo; Tissot, Cecile; Rivals, Isabelle; Gervais, Philippe; Caillé, Fabien; Moussion, Martin; Bottlaender, Michel; Sarazin, Marie (Journal of neurology, neurosurgery and psychiatry, 2022)
ObjectivesTo explore whether regional tau binding measured at baseline is associated with the rapidity of Alzheimer’s disease (AD) progression over 2 years, as assessed by the decline in specified cognitive domains, and the progression of regional brain atrophy, in comparison with amyloid-positron emission tomography (PET), MRI and cerebrospinal fluid (CSF) biomarkers.MethodsThirty-six patients with AD (positive CSF biomarkers and amyloid-PET) and 15 controls underwent a complete neuropsychological assessment, 3T brain MRI, [11C]-PiB and [18F]-flortaucipir PET imaging, and were monitored annually over 2 years, with a second brain MRI after 2 years. We used mixed effects models to explore the relations between tau-PET, amyloid-PET, CSF biomarkers and MRI at baseline and cognitive decline and the progression of brain atrophy over 2 years in patients with AD.ResultsBaseline tau-PET was strongly associated with the subsequent cognitive decline in regions that are usually associated with each cognitive domain. No significant relationship was observed between the cognitive decline and initial amyloid load, regional cortical atrophy or CSF biomarkers. Baseline tau tracer binding in the superior temporal gyrus was associated with subsequent atrophy in an inferomedial temporal volume of interest, as was the voxelwise tau tracer binding with subsequent cortical atrophy in the superior temporal, parietal and frontal association cortices.ConclusionsThese results suggest that tau tracer binding is predictive of cognitive decline in AD in domain-specific brain areas, which provides important insights into the interaction between tau burden and neurodegeneration, and is of the utmost importance to develop new prognostic markers that will help improve the design of therapeutic trials.